2012
DOI: 10.1111/j.1547-5069.2012.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review of Relationships Between Discrimination and Asian American Health

Abstract: Patient care providers can recognize discrimination as a significant stressor or purveyor of illness and explore ways to facilitate coping and resilience with their Asian American patients. Community-based participatory research approaches can be implemented by clinicians, academicians, and Asian American community partners to address the issue of discrimination and Asian American health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Social capital may provide the motivation, by means of obligation, reciprocity and self-control, to invest in future family health. There is a vast literature suggesting that experiencing different types of personal or institutional discrimination has detrimental effects on health, including nutritional risk (30,31) . In the present study it was revealed that intolerance of diversity had negative associations with the Mediterranean diet score and thus the healthy dietary patterns of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Social capital may provide the motivation, by means of obligation, reciprocity and self-control, to invest in future family health. There is a vast literature suggesting that experiencing different types of personal or institutional discrimination has detrimental effects on health, including nutritional risk (30,31) . In the present study it was revealed that intolerance of diversity had negative associations with the Mediterranean diet score and thus the healthy dietary patterns of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, Asian Americans have been under-represented in health research, and many studies that do include Asian Americans present aggregated data, masking critical health differences between ethnic subgroups. Disaggregated data demonstrate health disparities among subgroups on a number of chronic conditions, including cancer, heart disease, and mental health problems (Nadimpalli & Hutchinson, 2012). Factors contributing to deleterious health outcomes include limited health literacy, cultural and linguistic factors, and perceived discrimination (Clough, Lee, & Chae, 2013;Harris, 2012;Kandula, Kersey, & Lurie, 2004).…”
Section: Health Disparities Among Immigrant Groupsmentioning
confidence: 99%
“…13,[37][38][39] Among the five discrimination experiences included in EDS, two specific items, ''people act as if they think you are not smart'' and ''people act as if they are afraid of you,'' had a significant positive association with the greater frequency of healthcare use. Despite increased health service efforts to improve patient-centered models of care and shared decision-making, patients continue to feel required to assume socially sanctioned roles where the physician is the authoritarian.…”
Section: Discrimination Healthcare Use and Health Statusmentioning
confidence: 99%